Relationship Between Elderly Behavior With Visits To Elderly Posyandu In Pekanbaru Kota Area Year 2021 - Reny Juliana Sihombing (Sean Institute, 2021)
As the elderly population increases, the government is trying to formulate policies that aim to improve the health status and quality of the elderly to achieve a happy and efficient old age, in the family and community, but the visit of the elderly to the elderly Posyandu is still lacking, it is suspected that the elderly lack knowledge about the existence and benefits of the Posyandu elderly. The research objective was to determine the relationship between elderly behavior and the frequency of visits to posyandu. The research used was analytic in nature with a cross-sectional design on 45 sample people, conducted in PekanBaru Kota District from September 2020 to January 2021. Data on knowledge, attitudes and sample identity as data primary researchers collected by interview using a questionnaire, while the secondary data, namely the general description of the research location, was recorded from the Puskesmas report. Primary data were analyzed using univariate and bivariate, bivariate analysis with Chi-Square test. The results showed that there was a relationship between knowledge and the frequency of elderly visits to the elderly Posyandu with the results X2count > X2table, with a degree of confidence of 95% ∑ = 0.05 and df = 1, and there was no relationship between attitude and the frequency of visits by the elderly to the elderly Posyandu with results X2count <X2table. with a degree of confidence of 95% ∑= 0.05 and df= 1. It was concluded that visits by the elderly to the elderly Posyandu were related to the behavior of the elderly but it was concluded that visits to the elderly Posyandu were not related to the behavior of the elderly.